Structural characterization and antioxidant activity of polysaccharide from Rhodomyrtus tomentosa berry - Li, Dingjin; Wan Ibadullah, Wan Zunairah; Shukri, Radhiah; Duan, Qiuxia; Gu, Yipeng; Mustapha, Nor Afizah (Elsevier, 2025)
This study explored the structural properties and in vitro antioxidant activity of polysaccharide (RTP-1) from Rhodomyrtus tomentosa berry. The average molecular weight of RTP-1 is 11.638 kDa. Structural characterization revealed that the main chain of RTP-1 composed of 4,6)-β-D-Manp-(1 → and 6)-β-D-Manp-(1 → linkages, and the branched chain is the D-Galp-(1 → attached to the O-6 position of the glycan residue →4,6)-β-D-Manp-(1→). There is no triple helix structure in RTP-1. X-ray diffractometer results showed that RTP-1 is an amorphous semi-crystalline polymer with a characteristic “bun” shaped peak and a crystalline region at 20.42°. Atomic force microscopy results revealed that the average height of RTP-1 was 5.52 nm. The scanning electron microscopy results showed that RTP-1 exhibited a rough surface with numerous tiny pores. Thermo-gravimetry analysis and differential scanning colorimeter results revealed that RTP-1 was extremely thermally stable. The RTP-1 exhibited excellent 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), and OH radical scavenging activity.